Germinación de semillas y crecimiento inicial de plántulas de cedrela odorata (L) (cedro) en tres tipos de sustratos - Rodríguez Rendón, Janina Jessenia (2024)
Cedrela odorata is a versatile species with multiple uses and values, both economic and environmental, that make it important both for local communities and for the conservation of tropical ecosystems. The objective of the study is to identify the substrate that provides the most favorable conditions for germination and initial growth, crucial for the optimal development of plants. The methodology used included a completely randomized experimental design, with four treatments repeated four times. The variables evaluated were germination, survival, height, stem diameter and number of leaves of the seedlings. The substrates were prepared by mixing the specified components and Cedrela odorata (L) (cedar) seeds, using four types of substrates: S1 (Black earth 75% + sawdust 25%), S2 (Black earth 75% + rice husk 25% ), S3 (75% black soil + 25% sand) and S4 (Control - only black soil), were planted under controlled conditions. Dasometric measurements were carried out at regular intervals during the experiment to evaluate the growth and development of the seedlings. The results indicated that substrate S2, composed of black soil and rice husk, was the most effective, promoting superior growth in height, diameter and number of leaves compared to the other substrates. Substrates S2, S3 and S4 also showed the best results in terms of germination and survival. This study highlights the importance of properly selecting the substrate to optimize the germination and early development of cedar seedlings, which has significant implications for its cultivation and conservation.